Autecology and morphological properties of sandalwood (Santalum album) in Pidie District, Aceh, Indonesia - DEDEN NUROCHMAN; JUANG RATA MATANGARAN; GUNAWAN SANTOSA; DIDIK SUHARJITO; RITA KARTIKA SARI (Society for Indonesian Biodiversity, 2018)
Nurochman D, Matangaran JR, Santosa G, Suharjito D, Sari RK. 2018. Autecology and morphological properties of sandalwood (Santalum album) in Pidie District, Aceh, Indonesia. Biodiversitas 19: 406-412. IUCN Red List (1998) reported that Santalum album L. as an endangered species. Studies on autecology, association, and the utilization of sandalwood on its natural habitat becomes important to perform conservation of the species. This research was conducted in Teungku Dilaweung Village, Pidie District, Province of Aceh. Vegetation analysis was conducted to determine the population structures. Distribution pattern was analyzed using Morisita Index (Id) and Chi-square test, while interspecific association pattern was determined through contingency table, Jaccard Index (JI) and variance-ratio (VR) test. Observation and analysis of physical and chemical properties of soil, topography, and microclimate were done to identify ecological factors affecting the presence of sandalwood. The study showed that the highest abundance at tree level (IVI>100%) was obtained by Syzygium cumini with a density of 15 trees/ha. S. album was found to have clumped distribution pattern with an Id value of 2.258 and ?2compute of 62.571. S. Album has an interspecific association with two species i.e.: Syzygium cumini (?2compute of 5.104 and JI of 0.846) and Ziziphus oenopolia (?2compute of 6.516 and JI of 0.833) with VR of 0.474. Interspecific association indicated that S. album has strongly associated with Syzygium cumini and Ziziphus oenopolia. Morphological characters and habitat properties of sandalwood in research site has a similarity to the Province of NTT.